Analysis of sports supplements consumption in young Spanish elite dinghy sailors - Caraballo, I.; Dominguez, R.; Guerra-Hernandez, E. J.; Sánchez-Oliver, A. J. (Nutrients, 2020)
The sports performance of dinghy sailors is determined by their state of nutrition and hydration. Sports supplementation plays a prominent role in elite sailors, being essential in periods of competition due to its characteristics. This study aims to analyze the consumption of sports supplements (SS) in the different categories and groups of sailors based on the level of evidence, differentiating according to sex, competitive level, and type of boat. A total of 42 sailors from national and international levels and belonging to the Laser, 420, Techno-293 and RS:X classes participated in this study. They completed a questionnaire with questions about the consumption of SS and the possible repercussions on health and/or sports performance. The results were analyzed based on the different categorizations and group organization recently established by the Australian Institute of Sport (AIS), as well as by sex, level of competition and class to which the participants belonged. The male sailors and those who competed internationally had a higher prevalence in the consumption of SS. Among the classes of vessels studied, class 420 had the lowest SS consumption. SS intake was higher during competition days, regardless of sex or level of competition. Based on the classification established by the AIS, statistically significant differences were observed in sex, level of competition, and the type of boat.